Sublimation and Condensation at the Ice Sheet Surface of Mizuho Station, Antarctica (Special Issue of the Proceedings of the First Symposium on Antarctic Meteorology and Glaciology) - Yoshiyuki FUJII (National Institute of Polar Research, 1979)
Sublimation and condensation were estimated by three different methods, that is, atmometer, bulk formula and stake methods, at Mizuho Station from February 1977 to January 1978. The comparison of the three different methods of obtaining the sublimation rate in the summer of 1977-1978 showed a satisfactory agreement, especially in the weekly values. Condensation prevails in the period of five months from the middle of April to the middle of September and sublimation in the remainder seven months. The daily amount of sublimation showed its maximum, 92 mg/cm^2 on December 22 when the solar radiation was maximum. The annual amounts of sublimation and condensation are estimated to be 4.92 g/cm^2 and 0.19 g/cm^2 respectively. The present study implies that sublimation plays an important role in the heat and mass exchanges at the surface and in the metamorphism of surface texture.